Emprego de imagens landsat na análise temporal da linha de costa da porção oeste do estado do Ceará. - Souza, Cassiano Dias de (2019)
The Coastal areas of Ceará are on constant modification, both due to the action of Coastal dynamics and anthropogenic actions. The objective of this work was the analysis on the evolution of the coastline between the years 1984 and 2013 using digital image Processing techniques in images of satellites Landsat 5 (TM) and Landsat 8 (OLI). The study area is located between the Praia do Preá and the Rio Aracati-Mirim (municipality of Itarema), located on the west coast of Ceará, two units are predominate in the region: the FormaçãoBarreiras (Miocene/Pliocene), and Quaternary deposits (Holocene). After the georeferencing ofthe images, was used the software ArcGIS 10.2.2 for the Processing and vectoring. The RGB color compositions chosen were the 7-5-4 for the OLI sensor (Landsat 8), and 7-4-3 for the TM sensor (Landsat 5), both compositions help identify the emerged areas, emerged and flooded areas, bodies of water and vegetation. The region under study had a dynamic Coastal active, with intense migration of sand bar and several areas of erosion/deposition.